Analisis Pengadaan Bahan Baku dan Kinerja Produksi Agroindustri Kopi Bubuk Cap Kapal Lampung dan Agroindustri Kopi Bubuk Cap Intan - Murniati, Ktut; Lestari, Dwi Ayu; Kasymir, Eka (Journal of Food System & Agribusiness, 2023)
This research was conducted using a case study method that aims to conduct an analysis on the raw material procurement and production performance in the agroindustry of Kapal Lampung Brand ground coffee and the agroindustry of Intan Brand ground coffee in Bandar Lampung City. The two locations of this research were purposefully selected based on the purpose of comparing two ground coffee agroindustries that compete with each other in two different regions and the length of time since the business was established. Research data was collected for one month, from December 2021 to January 2022. Analysis of raw material procurement is carried out by qualitative descriptive analysis based on the six precise aspects of quantity, quality, place, time, price, and type. Analysis of production performance is carried out by quantitative descriptive analysis and qualitative descriptive analysis based on the aspects of productivity, capacity, quality, delivery speed, flexibility, and process speed. This research shows that the raw material procurement activities in two coffee powder agroindustries are not as precise as expected in terms of price. Overall, the production performance of both ground agroindustries does not belong in the good category.